Post-quantum encryption technology based on BRLWE for internet of things - Yitian GAO, Liquan CHEN, Tianyang TU, Yuan GAO, Qianye CHEN (网络与信息安全学报, 2022)
With the development of quantum computers, the classical public key encryption system is not capable enough to guarantee the communication security of internet of things (IoT).Because the mathematical puzzles which post-quantum encryption algorithms are based on cannot yet be broken by quantum computers, these new algorithms have good anti-quantum computing security.In particular, the lattice-based cryptography is expected to become the main technology of the next generation public key cryptosystem.However, post-quantum encryption algorithms have the disadvantages of large amount of computation and high storage space.The communication efficiency of IoT will be affected if post-quantum encryption algorithms are directly applied to the lightweight device under IoT environment.In order to better guarantee the communication security and improve the commutation efficiency of IoT, Sym-BRLWE (symmetrical binary RLWE) encryption scheme was proposed.Sym-BRLWE was improved from the existing post-quantum encryption scheme based on BRLWE (binary ringlearning with errors) problem.Specifically, Sym-BRLWE encryption algorithm met the efficiency requirements of IoT via improving the random number selection on the discrete uniform distribution and the calculation of the polynomial multiplication.Sym-BRLWE encryption algorithm achieved high efficiency and high security via adding encryption security precautions, then it is more suitable for IoT lightweight devices.From the security analysis, the proposed Sym-BRLWE encryption scheme had high security.It could theoretically resist lattice attacks, timing attacks, simple power analysis (SPA) and differential power analysis (DPA).From simulation experiments, which were carried out in a binary computing environment simulating an 8-bit micro-device, the proposed Sym-BRLWE encryption scheme has high efficiency and small key size in encryption and decryption.It could reduce the total encryption time by 30% to 40% when compared with other BRLWE-based encryption schemes with the parameter selection of the 140 bit quantum security level.